What does the international literature say about assessment practice for equitable learning outcomes for educationally disadvantaged high school students? - Townend, Geraldine; Alonzo, Dennis; Knipe, Sally; Baker, Sally (Frontiers in Education, 2025)
This systematic review examines the intersection of assessment and equity in education, with a particular focus on educationally disadvantaged students. Despite long-standing claims that assessment can enhance teaching and learning, little is known about assessment practices used in schools to increase educational outcomes for this student cohort. Drawing on international literature, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, we have identified inclusive assessments that support equitable practices, such as culturally responsive assessments, accessible assessments, and effective feedback practices. While these practices have been recognized for their potential to reduce bias and support fairer assessment, their implementation remains inconsistent and fragmented. In addition, our findings indicate that assessment design, assessment processes, teachers' assessment dispositions, knowledge, and skills, and policy influence the enhancement of equitable assessment. A notable gap is identified in the secondary education literature, along with an underrepresentation of studies from non-Anglophone contexts. Overall, our findings suggest the need for a more substantial investment in assessment-focused teacher education and development, as well as the integration of equity principles into policy frameworks. Addressing these gaps is essential to ensuring that assessment becomes a more effective tool for supporting educationally disadvantaged students.